KINERJA MANAJEMEN DAN STRATEGI PENGEMBAGNGAN LEMBAGA KEUANGAN MIKRO AGRIBISNIS SEDYO MAKMUR KABUPATEN BANTUL - RasyidaH Bakri; Lestari Rahayu Waluyati; Suhatmini Hardyastuti (Agro Ekonomi, 2014)
The aims of this study were to observe the performance of KSU LKM-A Sedyo Makmur between 2011-2013 and to formulate operated strategis for its future development. The performance indicator was portofolio quality, leverage, productivity, efficiency, profitability, financial feasibility, scale and depth of outreach, by means of World Bank approach of micro finance indicators. To formulate the strategies SWOT analysis was used.Result showed that performance of KSU LKM-A Sedyo Makmur was good on its leverage, productivity, efficiency, operational sel-sufficiency, and scale and depth of outreach between 2011-2013, bt its portofolio quality, profitability, and financial self sufficiency was still poor. For this study, the best SWOT strategy was the S-O that takes an advantage of the opportunity by using the strenghs. This can be done by add capital by leveraging existing network increase the offer of credit to customer/members who have good credit collectability, expand the market with regard to the principles of prudential financial institutions, and optimize the performance of loan officers to support market expansion and better members/potential customers management.